Deutsche Wirtschaft folgt stabilem Aufwärtstrend - Ferdinand Fichtner; Karl Brenke; Marius Clemens; Simon Junker; Claus Michelsen; Maximilian Podstawski; Thore Schlaak; Kristina van Deuverden (DIW Wochenbericht, 2016)
Die deutsche Wirtschaft dürfte, getragen von einer dynamischen Binnenkonjunktur, in diesem Jahr um 1,7 Prozent wachsen. Im kommenden Jahr schwächen sich der Konsum sowie die Bauinvestitionen ab, das Wachstum wird wohl 1,4 Prozent betragen. Der Außenhandel schiebt das Wachstum kaum an. In beiden Jahren des Prognosezeitraums werden die Kapazitäten in etwa normal ausgelastet; eine Überhitzung zeichnet sich nicht ab. Mittelfristig sind aber kräftigere Investitionen in den Kapitalstock erforderlich, um das Wachstumspotential der deutschen Wirtschaft zu erhöhen. – – Supported by dynamic domestic development, the German economy is expected to grow by 1.7 percent this year. As consumption and investment in construction are likely to weaken in the coming year, growth in 2017 should amount to roughly 1.4 percent. Foreign trade is contributing relatively little to growth. In both years of the forecast period, capacities will be at more or less normal levels of utilization; there are no signs of overheating. In the medium term, however, stronger investment in the capital stock is necessary to increase the growth potential of the German economy.
Keywords: E32; E66; F01; 330; business cycle forecast; economic outlook